A STUDY ON ETHICAL CONSIDERATIONS IN AI DEPLOYMENT - Dr. S. Sarumathi (Journal of Management and Science, 2026)
The rapid advancement and deployment of artificial intelligence (AI) systems have raised critical ethical considerations that must be addressed to ensure their responsible use. This article explores key ethical challenges in AI deployment, with a particular focus on fairness, transparency, and accountability. Fairness is central to preventing biases that can lead to discrimination and inequities in decision-making, while transparency is vital to fostering trust and enabling stakeholders to understand how AI systems make their decisions. Additionally, the article examines other ethical concerns, such as privacy, autonomy, and the potential for unintended harm, offering a comprehensive framework for addressing these issues. By critically evaluating current approaches and proposing best practices, the article aims to provide guidance for developers, policymakers, and organizations in deploying AI technologies that align with ethical principles and contribute to the well-being of society.